The interprofessional nurse-physician model in comprehensive management of chronic hepatitis B: An updated review - Xiao-Ling Xiang; Fa-Da Wang; Xi-Jia Luo; Hui Chen; Ting-Ting Zheng; Cheng-Run Song; Yu-Jing Li; Sahar Muzammal; Jing Zhou; Xue-Zhong Lei; Rong Deng; En-Qiang Chen (Journal of Virus Eradication)
Chronic hepatitis B (CHB) remains a significant global public health challenge, particularly in China, where it affects over 70 million individuals. The outpatient management of CHB patients is complex due to the chronic nature of the disease, the requirement for long-term follow-up, and the socioeconomic and cultural diversity of patients. The interprofessional nurse-physician model has emerged as a promising strategy to address these challenges by fostering interprofessional collaboration, leveraging technology, and delivering patient-centered care. This review synthesizes recent literature and case studies to evaluate the application, benefits, and limitations of this model in CHB management. Findings indicate enhanced health education, treatment adherence, and patient outcomes. However, further improvements are required in interprofessional communication, reducing health disparities, and integrating advanced technologies. This review provides both theoretical insights and practical recommendations to optimize the nurse-physician model for improving CHB patient well-being.